2011
DOI: 10.1158/1055-9965.epi-10-0636
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study on Overweight, Smoking, Alcohol Consumption, and Risk of Barrett's Esophagus

Abstract: Background: Barrett's esophagus (BE) is a precursor lesion of esophageal adenocarcinoma. Besides gastroesophageal reflux, possible risk factors for BE include overweight, cigarette smoking, and alcohol consumption. Our objective was to study these associations by using prospective data.Methods: The prospective Netherlands Cohort Study, initiated in 1986, consists of 120,852 men and women, aged 55 to 69 years at baseline. At baseline, all subjects completed a questionnaire on dietary habits and lifestyle. After… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 42 publications
5
46
0
1
Order By: Relevance
“…For example, over 70% of the Japanese subjects had a BMI <25.0 [29], while in contrast over 70% of individuals in the USA had a BMI >25.0 [48]. Regarding the relationship between BMI and BE formation, we found a positive association between the two factors, consistent with previous reports from Western countries [38,39,40,41,49]. Further, we identified even slightly overweight subjects (BMI 23.0-24.9) as having an independent risk factor for BE, in contrast with previous reports from Western countries in which a BMI >25.0 or >30.0 has been associated with BE [38,39,40,41,49].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, over 70% of the Japanese subjects had a BMI <25.0 [29], while in contrast over 70% of individuals in the USA had a BMI >25.0 [48]. Regarding the relationship between BMI and BE formation, we found a positive association between the two factors, consistent with previous reports from Western countries [38,39,40,41,49]. Further, we identified even slightly overweight subjects (BMI 23.0-24.9) as having an independent risk factor for BE, in contrast with previous reports from Western countries in which a BMI >25.0 or >30.0 has been associated with BE [38,39,40,41,49].…”
Section: Discussionsupporting
confidence: 89%
“…We found increased BMI to be an independent risk factor for BE in addition to the well-recognized GERD-related risk factors such as heartburn and hiatal hernia. Although BMI >25 or >30 have sometimes been identified as an increased risk factor for BE in Caucasian populations [38,39,40,41], this study clarified that even slightly overweight Japanese subjects with a BMI of 23.0-24.9 have a significantly increased risk of BE, suggesting that the Japanese are predisposed to BE at lower BMI compared to Caucasian populations. In addition, there seemed to be gender-related differences in the association between BMI and BE, i.e.…”
Section: Discussionmentioning
confidence: 62%
“…However, the association between alcohol intake and esophageal adenocarcinoma (EAC) is attenuated. The two cohort studies by Steevens et al (17,30) revealed that alcohol consumption did not promote the risk of developing EAC or Barrett's esophagus (precancerous lesions of EAC). Other analyses reached similar conclusions (29,31,32).…”
Section: Subtypes Of Esophageal Cancermentioning
confidence: 98%
“…Pre-existing diabetes may increase the risk of mortality by as much as 40% in people with cancer [43]. While gastroesophageal reflux and high body mass index are known as well established risk factors for esophageal cancers [44][45][46], it has also reported that diabetes was associated with substantial and a significant increased risk of esophageal adenocarcinoma [47][48][49][50][51].…”
Section: Ampk Pathway As a Target For Esophagus Cancer Treatmentmentioning
confidence: 99%